Collaboration public-privé : les rencontres de football professionnel comme métamodèle et le Paris Saint-Germain comme exemple - Rahib, S.; Bodin, D. (Movement & Sport Sciences - Science & Motricité, 2021)
Public-private collaboration in the area of securing sports events has been implemented relatively recently. Most of the time, it has been the subject of legal regulation, following incidents that had to be progressively prevented, and of a regulation that has been built up with regard to the laws and directives enacted. Two phases can be observed. The first, which corresponds to the genesis of this cooperation imposed by the laws. The second, more strategic, sees different goals for public-private players, even if the objective of security remains the same. This increased collaboration has also been built on the basis of each party`s own goals: rationalization of State action and public spending on the one hand, and a marketing drive aimed at commercial expansion and the creation of a brand image on the other. Professional soccer is a kind of metamodel at this level and Paris Saint-Germain is a particular example. Laws, directives and regulations have been studied based on a chronological analysis of the documents and archives constituting the legal and regulatory framework gradually put in place over the last 60 years.